Research on Low-Carbon Development Path for Key Energy-Consuming Hospitals Under the "Dual Carbon" Background - Yang, Qisheng, (Journal of Innovative Studies, 2024)
Before delving into the background and significance of the "dual carbon" goals, it is essential to briefly elaborate on their connotations. The "dual carbon" goals typically refer to two objectives: "carbon peaking" and "carbon neutrality," which correspond to the highest point of carbon dioxide emissions and the ultimate state of net-zero emissions, respectively. Carbon peaking denotes the point in time when carbon dioxide emissions reach their peak within a certain period and then gradually decline. Carbon neutrality, on the other hand, refers to the point in time when, through measures such as emission reduction and increasing carbon sinks, carbon dioxide emissions and absorptions reach a balanced state, achieving net-zero emissions.